2019
DOI: 10.3390/ijerph16111936
|View full text |Cite
|
Sign up to set email alerts
|

How Personal Perspectives Shape Health Professionals’ Perceptions of Fetal Alcohol Spectrum Disorder and Risk

Abstract: This article examines how health, allied health and social service professionals’ personal perspectives about alcohol and the risks associated with alcohol consumption become non-clinical factors that may influence their professional practice responses in relation to fetal alcohol spectrum disorder (FASD). It presents findings derived from a qualitative, interview-based study of professionals from a range of health, allied health and social service professions in New Zealand. The data derived from these interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…Finally, this study also found many cases of combined substance misuse among parents of children suspected with FASD, similar to the research by Bagley and Badry (2019). The combined impact of substance misuse and adverse socio-environment act in concert to complicate the chances of obtaining a FASD diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, this study also found many cases of combined substance misuse among parents of children suspected with FASD, similar to the research by Bagley and Badry (2019). The combined impact of substance misuse and adverse socio-environment act in concert to complicate the chances of obtaining a FASD diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…We, as editors of this special issue on Fetal Alcohol Spectrum Disorders (FASD), are proud to present eleven papers [1,2,3,4,5,6,7,8,9,10,11]. These studies focused on prevention, systems development, clinical practice, and public policy.…”
mentioning
confidence: 99%
“…On a professional level, having conversations about alcohol use during pregnancy with friends and clients is often difficult to navigate. When having these conversations, professionals will often draw upon their own personal experiences and social/relational perspectives to bridge the conversation with their clients (Bagley & Badry, 2019). Professionals needing to bridge conversations using their own experience could be because there is no mandatory training or best practices in relation to FASD in the human service setting, and/or because a practitioner has their own experiences outside of the profession that shapes their responses to it (Bagley & Badry, 2019).…”
Section: Stigma Associated With Fasdmentioning
confidence: 99%
“…When having these conversations, professionals will often draw upon their own personal experiences and social/relational perspectives to bridge the conversation with their clients (Bagley & Badry, 2019). Professionals needing to bridge conversations using their own experience could be because there is no mandatory training or best practices in relation to FASD in the human service setting, and/or because a practitioner has their own experiences outside of the profession that shapes their responses to it (Bagley & Badry, 2019). Relating non-clinical experiences in a clinical setting is not inherently a bad thing, however a medical professional's bias and attitudes towards who is seen to be "at risk" for having FASD can have serious implications for whom they deem fits the criteria for an FASD assessment (Bagley, 2019).…”
Section: Stigma Associated With Fasdmentioning
confidence: 99%